Congenital chloride diarrhoea in a Chinese infant with a compound heterozygous SLC26A3 mutation - Qian Li; Jing Wang; Ruixian Zang; Lichun Yu; Zhenle Yang; Shuzhen Sun (BMC, 2024)
Abstract Introduction Congenital chloride diarrhoea (CCD) is an autosomal recessive condition that causes secretory diarrhoea and potentially deadly electrolyte imbalances in infants because of solute carrier family 26 member 3 (SLC26A3) gene mutations. Case presentation A 7-month-old Chinese infant with a history of maternal polyhydramnios presented with frequent watery diarrhoea, severe dehydration, hypokalaemia, hyponatraemia, failure to thrive, metabolic alkalosis, hyperreninaemia, and hyperaldosteronaemia. Genetic testing revealed a compound heterozygous SLC26A3 gene mutation in this patient (c.269_270dup and c.2006 C > A). Therapy was administered in the form of oral sodium and potassium chloride supplements, which decreased stool frequency. Conclusions CCD should be considered when an infant presents with prolonged diarrhoea during infancy, particularly in the context of maternal polyhydramnios and dilated foetal bowel loops.